2010
DOI: 10.1080/00220270903403189
|View full text |Cite
|
Sign up to set email alerts
|

Pupil perspectives on the purposes and benefits of studying history in high school: a view from the UK

Abstract: Drawing on data from 1740 pupil questionnaires and 160 pupils in focus‐group interviews, the study aimed to gain insight into British pupils’ ideas about why they study history at school. The paper considers the implications of these ideas for history teachers and teacher educators. The data suggest that many pupils have very vague ideas about the purposes of school history. The variations among schools suggested that there are things that teachers can do to explain the purposes and benefits of school history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 17 publications
1
37
1
5
Order By: Relevance
“…The comments from the students are unlikely to reflect the perspectives of their teacher to any great extent since they had only recently been taught by them, although it is possible that they may reflect the views of their previous teachers [23].…”
Section: The Researchmentioning
confidence: 99%
“…The comments from the students are unlikely to reflect the perspectives of their teacher to any great extent since they had only recently been taught by them, although it is possible that they may reflect the views of their previous teachers [23].…”
Section: The Researchmentioning
confidence: 99%
“…In a couple of these respects, history encounters difficulties. According to Haydn and Harris (2010), many students do not fully appreciate the purposes of studying history, nor, according to a QCA report (2005) are they able to relate it to future employment prospects (beyond obviously history-specific jobs such as history teacher and archaeologist). If students are also looking for an 'easy' subject then the perception of history as an 'academic' subject may be a barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Their report also showed that 2/3 of pupils would drop history at the age of 14, characterising it as 'hard' due to an excess of memorising and essay writing, boring with little or no relevance, and therefore seeing little point in studying it. Pupils are reported to have difficulties in defining why learning history was useful (Haydn, 2005;Haydn and Harris, 2010). The same attitude could possibly be expected for prehistory.…”
Section: Relevance (Fits With Children's Everyday Use Of Technology)mentioning
confidence: 99%
“…The same attitude could possibly be expected for prehistory. Therefore, a well-planned introduction of technology that recruited history and archaeology data, if supported by explanations and experiential demonstration of subject's purpose could enhance students' motivation and enthusiasm (Haydn and Harris, 2010). It could also support students' understanding across subjects and topics, seeing their inter-connectedness.…”
Section: Relevance (Fits With Children's Everyday Use Of Technology)mentioning
confidence: 99%